The Relationship Between Parenting Patterns And Fine Motor Development In Preschool Age Children (5-6 Years) - Sartika, Wiwi; Risa Andela; Brilian Dini MA Iballa (Universitas Prima Indonesia, 2025)
Parenting style refers to the way parents treat, educate, guide, and discipline their children to support their maturation process and help them internalize societal norms. Disruptions in fine motor development can lead to learning difficulties, developmental delays, and growth that is not age-appropriate. According to 2020 data from the World Health Organization (WHO), 15–20% of preschool-aged children experience fine motor development disorders. In Riau Province, in 2022, about 5–10% of preschoolers were reported to have delayed fine motor development. The purpose of this study was to determine the relationship between parenting styles and fine motor development in preschool-aged children (5–6 years). This research method employed a quantitative method with a correlational analytic design using a cross-sectional approach. The instruments used were questionnaires and the Pre-Screening Developmental Questionnaire (KPSP). The population consisted of 52 individuals, with a sample size of 36 respondents. showed a p-value of 0.006 (< α 0.01), indicating a significant relationship between parenting styles and fine motor development in preschool-aged children (5–6 years) at TK Islam Masjid Raya, Pekanbaru City. So, the majority of the respondents practiced a democratic parenting style (19 respondents or 52.8%), and 14 children (38.9%) were found to have normal fine motor development.